Adapting Genetic Methods For Transposon Mutagenesis And Fluorescent Markers In Borrelia - Weber, Peter (Jihočeská univerzita, 2020)
The aim of this Bachelor thesis was the examination and generation of different mutants in various Borrelia species. While several assays were used to examine aspects of B. burgdorferi transposon mutants, genetic tools were applied in order to generate fluorescent markers in B. afzelii and a vector construct in B. burgdorferi. This work should provide an overview of various genetic methods and their methodology that have been developed in Borrelia bacteria.
Adapting Genetic Methods For Transposon Mutagenesis And Fluorescent Markers In Borrelia
Keywords: Borrelia; Green Fluorescent Protein; Transposon Mutagenesis; Swarm Motility Assay; Plasmid Screening; Lyme disease; Borrelia; Green Fluorescent Protein; Transposon Mutagenesis; Swarm Motility Assay; Plasmid Screening; Lyme disease